Educação ambiental: vivências socioculturais e visões de estudantes e educadores, Acará-PA - ALVES, Eliene da Silva (2019)
The interactions between individuals and natural environment are essential to promote an environment education that respects, both, human and global nature. This study elaborates on the awareness EJA students and educators at Prof. Deusalina da Cunha e Sousa Carneiro High School, in Acará (PA), have of environment education and its practices. This is an empirical and bibliographical study, with theorical references on the subject, observation of the space surrounding the school, and a research with the school educators and EJA students as methodology. The results point to a foreign concept to the actual practice, where students understand the importance of human and global nature, however, their daily experiences in the subject is minimum, differently from the community around the school, where they predominantly act on nature, showing that a regular environment practice exists, yet, it has little recognition amongst city dwellers and the local public power.